Antibacterial Test of Binahong Leaf Extract Ointment (Anredera cordifolia) Against Staphylococcus aureus Bacteria from Diabetic Wounds - Risa Umami; Riwayati Malika (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2020)
Diabetes mellitus (DM) is characterized by an increase in glucose levels in the blood due to disorders of glucose metabolism in the body. The pancreas organ of people with DM has a weakness in producing the hormone insulin. As a result, the distribution of blood glucose to other organs of the body is inhibited so that glucose levels in the blood increase which causes DM sufferers to experience longer wound healing than normal humans. Binahong leaves contain alkaloids, saponins and flavonoids which have antibacterial activity which can accelerate the wound healing process. The purpose of this study was to determine the antibacterial effect of binahong leaf extract ointment (Anredera cordifolia) against Staphylococcus aureus bacteria from diabetic wounds. This research includes antibacterial test for binahong leaf extract ointment (Anredera cordifolia) with variations in the concentration of 10%, 20%, and 30% of the concentration of binahong leaf extract of 25% which resulted in a wound coverage percentage of up to 100%, namely at 30% ointment concentration. The conclusion of this study is that there was no wound closure for negative control and positive control in the form of oxytetracycline, the percentage of wound closure was 85%.